Supervisor's Survival Kit: Your First Step into Management, Ninth Edition - Chapman, Elwood; Goodwin, Cliff (Pearson, 2001)
SUPERVISOR'S SURVIVAL KIT, NINTH EDITION continues the successful tradition of preparing today's workforce for the first steps into management. Solve problems through Mini-Games. Create a motivating work environment. Lead effective work-team behavior. Improve interpersonal communication between employees.